Optimizing energy audits for K-12 educational facilities - Gentry, Rebecca M. (Kansas State University, 2012)
Conserving energy and minimizing utility consumption are primary focuses in educational facilities because annual budgets are often limited. Consequently, building energy audits are an effective tool to assist in evaluating existing buildings and identify methods of reducing annual energy use. Therefore, this report describes what building energy audits are, how they can be performed, and how to discover energy saving measures from the results. Specifically, the research considers physical building features and building operations and evaluates them for possible modification to reduce energy use. Proposed solutions vary from no-to-low cost options to larger capital investments. The research also analyzes building components for economic viability using the net present cost and payback period as the basis of comparison, permitting recommendations. The audit procedure and the economic analyses are presented in a manner that allows individual educational facility managers to assess their own buildings.
Keywords: Energy audits; K-12 educational facilities; Architectural engineering (0462); Engineering (0537)